The Roles of Teachers in Improving Students Islamic Behaviour at SMA Negeri 1 Kasihan - Dewa Ikhram (Journal of Islamic Education and Ethics, 2023)
Islamic behavior is an important foundation for students for their life and future. The current phenomenon is that there are students who have not implemented Islamic behavior yet, such as not attending classes (ditching classes), violating the rules set by the school, and not participating in programs to improve their Islamic behavior, such as tausiyah/dawah and congregational prayers at school. This research aims to find out the Islamic behavior of the students at SMA (Senior High School) Negeri 1 Kasihan, analyze the efforts done by the school in improving the Islamic behavior of its students, and find out the supporting or inhibiting factors faced by the teachers in improving the Islamic behavior of the students. This is descriptive qualitative research using snowball sampling as the data collection technique. Snowball sampling technique is a technique to determine the sample which is initially small in number so that the number of the sample becomes bigger. Phenomenology is used as a research model. The findings show that the students of SMA N 1 Kasihan have proven to have better Islamic behavior.